Clinical care of children with primary ciliary dyskinesia. (3rd October 2017) - Lucas, Jane S.; Alanin, Mikkel Christian; Collins, Samuel; Harris, Amanda; Johansen, Helle Krogh; Nielsen, Kim G; Papon, Jean Francois; Robinson, Phil; Walker, Woolf T.
ABSTRACT: Introduction : Primary ciliary dyskinesia (PCD) is a rare heterogeneous disorder, usually inherited as an autosomal recessive condition but X-linked inheritance is also described. Abnormal ciliary function in childhood leads to neonatal respiratory distress in term infants, persistent wet cough, bronchiectasis, chronic rhinosinusitis, and hearing impairment; approximately 50% of patients have situs inversus . There is a paucity of evidence for treating PCD, hence consensus guidelines are predominantly influenced by knowledge from cystic fibrosis (CF). Extrapolation of evidence from other diseases is inappropriate since differences in pathophysiology, morbidity and prognosis risk treatment failure and lack of adherence. Areas covered : Review authors searched PubMed and Cochrane databases for publications relating to management of children with PCD. Because of the paucity of data, we emphasise the need for well-designed clinical trials with PCD patients rather than reliance on evidence from other diseases. Expert commentary : The evidence for treatment of PCD is poor, and management is often extrapolated from studies of patients with CF or chronic rhinosinusitis. However, much work is underway to improve the situation and international consortia and networks are conducting well-designed projects to inform the management of children with PCD.